Traditional Education: Methods and Finality in Chinua Achebe’s Things Fall Apart (1958) and Arrow of God (1969) - Babacar DIAKHATÉ (BIRCU, 2021)
Before colonization, Africans had their own ways and methods of education. Its finality was to educate their children in accordance with African values. In Things Fall Apart and Arrow of God, Chinua Achebe shows that African traditional education plays a key role in the passage from childhood to adulthood. Instead of using western materials and tools such as classrooms, blackboards, talks and or pens, in African traditional education the fireplaces, the farms, storytelling, tales and proverbs were the methods and means that African wise people adopted to educate their children.